The Expectations and Challenges of a New Generation Leader - Dorota BALCERZYK (Communications of International Proceedings, 2020)
The publication deals with an intergenerational team's conditions and specificity that pose a challenge for a manager with leadership ambitions. The article aims to provide a research report. It presents the perspective of the millennial generation (Gen Y) and its expectations towards the leader. The research results are part of the search for new directions of leadership. In the digital age, expectations towards a leader are surprisingly traditional. Authenticity, social competencies, shared values, and trust turn out to be priorities for the young generation.
Keywords: Leadership; Leader; Generational Cohorts; Generation Y; Trust.